Chemical Properties and Recovery of Vermicompost from Mixed Shredded Leaves and Poultry Manure Using Eudrilus eugeniae Under Different Loading Schemes - Bulfa, Jr., Arsenio D.; Cubelo, Jose Edwin C. (Silliman Journal, 2022)
Vermicomposting is a simple biotechnological procedure to produce excreta of earthworms called vermicompost. Vermicompost contains a high concentration of nutrients that are capable of improving soil health and quality. However, the complexity of interacting factors that affect vermicomposting is not yet fully understood. A study laid out in a completely randomized design was conducted to identify the effects of different loading schemes of mixed shredded leaves (SL) and poultry manure (PM) to vermicompost recovery and chemical properties using the Eudrilus eugeniae, a litter-dwelling species of earthworm which can consume and mix a large amount of soil and organic matter (OM) and convert it into fertile casts. Results showed the improved chemical properties of vermicomposts such as pH, organic matter (OM), available N, available P, and exchangeable K. A significant difference was also observed in pH, N, P, and K. The frequent loading that causes a sudden rise in pile temperature increased the mortality of earthworms affecting vermicompost recovery. Overall, the recovery was still high from all treatments based on the capability of the initial number of earthworms placed in each vermicomposting container to produce vermicompost.